1995
DOI: 10.1038/nm1095-1074
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel dual angiotensin II/vasopressin receptor on the basis of molecular recognition theory

Abstract: The molecular recognition theory suggests that binding sites of interacting proteins, for example, peptide hormone and its receptor binding site, were originally encoded by and evolved from complementary strands of genomic DNA. To test this theory, we screened a rat kidney complementary DNA library twice: first with the angiotensin II (AII) followed by the vasopressin (AVP) antisense oligonucleotide probe, expecting to isolate cDNA clones of the respective receptors. Surprisingly, the identical cDNA clone was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
1
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 44 publications
5
70
1
1
Order By: Relevance
“…This indicates that the occupation of the ANG II AT 1 receptor plays a role in the regulation of vasopressin-regulated AQP2 expression in collecting ducts and urine concentration in vivo. Moreover, the dual ANG II/AVP receptor, which is a novel receptor coupled to adenylate cyclase that responds with equal sensitivity to ANG II and AVP, has been isolated (49). The renal immunocytochemical distribution of the ANG II/AVP receptor to IMCDs also strongly suggests the role of ANG II in the regulation of vasopressin-regulated AQP2 expression in the collecting ducts and urine concentration in vivo (17).…”
Section: Occupation Of Ang II At 1 Receptor Plays a Role In Regulatiomentioning
confidence: 99%
“…This indicates that the occupation of the ANG II AT 1 receptor plays a role in the regulation of vasopressin-regulated AQP2 expression in collecting ducts and urine concentration in vivo. Moreover, the dual ANG II/AVP receptor, which is a novel receptor coupled to adenylate cyclase that responds with equal sensitivity to ANG II and AVP, has been isolated (49). The renal immunocytochemical distribution of the ANG II/AVP receptor to IMCDs also strongly suggests the role of ANG II in the regulation of vasopressin-regulated AQP2 expression in the collecting ducts and urine concentration in vivo (17).…”
Section: Occupation Of Ang II At 1 Receptor Plays a Role In Regulatiomentioning
confidence: 99%
“…The stimulatory effect of Ang-(1-7) on water permeability in this nephron segment is dose-dependent, can be blocked by A-779 and, interestingly, also by an AVP-V 2 receptor antagonist (Magaldi AJ, personal communication). Regarding this last observation, it would be interesting to explore the involvement of the recently described AVP-angiotensin receptor (50) in the renal effects of Ang-(1-7). In contrast to the dose-related increase of water reabsorption induced by Ang-(1-7) in IMCD (22), in the frog skin the heptapeptide alters osmotic permeability biphasically, increasing it at low concentrations (1 nM) and decreasing it at higher concentrations (10 nM) (21).…”
Section: Tubular Effectsmentioning
confidence: 99%
“…The molecular basis for such interactions has not been elucidated to date, although several models have been proposed (19,24). MRT has successfully been used to identify the dual angiotensin-vasopressin receptor (25) and the prion receptor (30). We have demonstrated that there are several peptide motifs, each of which has multiple ASP sites within a protein molecule, and we designated such motifs antisense homology boxes (AHBs) (2).…”
Section: Discussionmentioning
confidence: 99%
“…This theory is based on the observation that there is a tendency in the genetic code for codons of hydrophilic amino acids to be complemented on the complementary DNA strand by codons for hydrophobic amino acids and vice versa. In spite of ambiguities concerning the universality of the interactions involved in the binding of complementary peptides, the number of reports on complementary peptide pairs has been increasing (2,12,14,15,25,28,30,38). Furthermore, we have suggested that sense and antisense peptide interactions may be involved in the generation and maintenance of the tertiary structure of proteins (2).…”
mentioning
confidence: 99%